Novel modification of activated charcoal sheet with N-methylpolypyrrole and silver nanoparticles for removal of hexavalent chromium in water treatment processes - Duhan Surender; Chandra Mohan; Rakesh Kumar (Zaštita Materijala)
The novel NPPY-AgNP's@AC CPN were synthesized and used for batch mode reductive adsorption of hexavalent Chromium (Cr+6) ions in water treatment processes. The Activated Charcoal (AC) sheet was firstly encapsulated with silver nanoparticles (AgNP's) by in-situ reduction method and capped with N-methylpolypyrrole (NPPY) to obtain NPPY-AgNP's@AC conducting polymer nanocomposites (CPN). The obtained CPN were characterized by HRFESEM, XRD, FTIR, and EDS. The nanocomposite materials showed excellent Cr+6 ions adsorption efficiency (Ad%) of 97.8% with adsorption capacity (qe) of 340 mg/g. The impact of various parameters like pH, adsorbent dose, initial Cr+6 ions concentration, temperature, and contact time on Ad% and qe were evaluated. The recycling experiments of NPPY-AgNP's@AC CPN revealed their enhanced reuse performance and could be utilised for five consecutive cycles without suffering much reductions in their initial efficacy. The novel PPY-AgNP's@AC CPN seems to be highly efficient materials for Cr+6 ions removal from polluted water.